Pulmonary Spindle Cell Carcinoma Presenting Anaplastic Lymphoma Kinase Rearrangement - Kei Sonehara; Shuhei Nozawa; Yusuke Suzuki; Taisuke Araki; Masamichi Komatsu; Kazunari Tateishi; Masayuki Hanaoka (Case Reports in Oncology, 2023)
Pulmonary spindle cell carcinoma is a subtype of pulmonary sarcomatoid carcinoma and a very rare tumor type with a poor prognosis. A few case reports have documented patients with pulmonary sarcomatoid carcinoma with anaplastic lymphoma kinase rearrangement, and the efficacy and outcomes of anaplastic lymphoma kinase inhibitors remain unclear. Herein, we present the case of a 60-year-old woman with stage IVB disease who was diagnosed with a metastatic brain tumor. This patient showed high levels of programmed cell death ligand 1 expression and anaplastic lymphoma kinase rearrangement and received pembrolizumab as the first-line treatment. Three weeks later, pembrolizumab failed to reduce the size of the primary pulmonary tumor, and the patient’s general condition did not improve. The patient received alectinib as the second-line treatment. Two months later, multiple brain metastases were observed. Hence, whole-brain irradiation was performed as treatment for multiple brain metastases, while another anaplastic lymphoma kinase inhibitor was administered; however, both treatments remained ineffective. The patient eventually died 9 months after the initiation of first-line treatment. The present case report describes the therapeutic course of a patient with pulmonary spindle cell carcinoma with an anaplastic lymphoma kinase rearrangement.